PERILAKU ORANG TUA DALAM TOILET TRAINING PADA TODDLER: STUDI KASUS ANAK DENGAN DEMAM BERDARAH DI RSD BALUNG JEMBER - Riswanda Putri Khusnul Khotimah; Nikmatur Rohmah (Forind Press, 2026)
Parental behavior during toilet training plays a crucial role in supporting elimination independence in toddlers aged 1-3 years. Illness, particularly Dengue Hemorrhagic Fever (DHF), affects the consistency of toilet training because parents' attention is more focused on the child's health condition. This study aimed to describe parental behavior in toilet training for toddlers with DHF at RSD Balung Jember, covering aspects of knowledge, attitude, and practice. A descriptive case study design was used with two parents as subjects. Data were collected through observation, interviews, and questionnaires. Results showed that both respondents had good knowledge and positive attitudes; however, the practical implementation of toilet training was not yet optimal due to the child's weakened physical condition during treatment. Support from healthcare workers through education and guidance is needed to ensure toilet training can still be carried out consistently during hospitalization.